Determinants of the Effectiveness of Risk Management Implementation with Organizational Culture as a Moderating Variable - Rinaldi, Rinaldi; T, Sutrisno; Prihatiningtias, Yeney Widya (AIBPM Publisher, 2024)
This study aims to investigate the impact of human resources, budget allocation, and regulations and policies on the effectiveness of risk management implementation, with organizational culture as a moderating variable. The research employs a survey-based quantitative approach, utilizing questionnaires distributed to employees in Echelon II Work Units at the Head Office of the Ministry of Public Works and Housing. Data analysis is conducted using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The findings indicate that human resources, budget allocation, and regulations and policies positively influence the effectiveness of risk management implementation. Furthermore, organizational culture does not enhance the positive effect of human resources on the effectiveness of risk management implementation. However, it diminishes the positive effect of the budget and amplifies the influence of regulations and policies on the effectiveness of risk management implementation.